Distribuição altitudinal dos morcegos da Serra do Caparaó - Ulian, Carina Maria Vela (2023)
The present study presents the characterization of the chiropterofauna present in the Parque Nacional do Caparaó (PNC) and the evaluation of how bat species and trophic guilds are distributed along the altitudinal gradient. The PNC region, in southeastern Brazil, concentrates the highest elevation of the Atlantic Forest, reaching 2,892 m (Pico da Bandeira). Despite being one of the most representative protected areas of the high-altitude Atlantic Forest, the chiropterofauna of the Caparaó region remains practically unknown. In these areas, altitudinal gradients are responsible for potentially abrupt changes in biological communities, mainly due to changes in temperature and humidity, influencing flora and fauna. For bats, communities at higher altitudes are expected to be composed mainly of aerial insectivorous bats due to resource availability and lower physiological limitations. In Brazil, studies on bats from regions of high altitude, above 2,000 m, are rare, with most studies being carried out in regions with altitudes below 1,500 meters. In order to understand how the bat community behaves in this region, the 2,000 m elevation of the PNC was divided into four ranges (from 800 to 2,800 m) and two sampling methods were used: mist-nets and ultrasound recordings. The data obtained were analyzed for richness, variation in composition and influence of altitude on the distribution of species and trophic guilds. Thirty-five species were recorded, 15 using mist nets and 23 using bioacoustic recordings, with only three species recorded using both methods. The records obtained include two new species for Espírito Santo, Myotis izeckshoni (mist-net) and Molossops temminckkii (bioacoustics). Additionally, the results show the need to use more than one method of recording bats to characterize the fauna, given that individually, both nets and recordings have limitations and may underestimate species richness, being complementary methods. There was a linear decline in bat richness with increasing elevation, with the aerial insectivores guild being widely distributed along the gradient and the only one present at higher altitudes. It was also detected that the variation in composition is due to the nesting of species, with 62% similarity between the lowest and highest areas, indicating the presence of subsets with ordered loss of species along the gradient. This work emphasizes the relevance that fauna and flora 7 inventories have for the characterization of ecological and biogeographical patterns of communities in high altitude areas, in addition to contributing to discussions involving environmental pressures arising from anthropic and climate changes that interfere with the maintenance and preservation of regions hilly.